A novel total fatigue life model for delamination growth in composite laminates under generic loading. (15th February 2021) - Yao, Liaojun; Cui, Hao; Guo, Licheng; Sun, Yi
Abstract: It is really important to have a reliable model to represent fatigue delamination growth (FDG) behavior for composite structural design and life evaluation with the wide applications of composites in aerospace industry. Therefore, a new total fatigue life model for delamination growth in composites has been proposed for engineering in present study, according to introducing a new crack similitude parameter and using the total life strategy. It clearly demonstrates that the FDG behavior under various fatigue loading conditions in the entire strain energy release rate ( SERR ) range can be appropriately characterized with this model. Particularly, a master resistance curve can be obtained to determine the FDG behavior under various R -ratios at a given mode mixity. And these resistance curves can shift downwards with mode mixity. This model will be important for material characterization, comparison and development, which is prerequisite for the applications of the damage tolerance philosophy in composite structural design and life evaluation of a composite structure.